VD_FINDINFO Jug / 2021 / 380 vom 17. Mai 2021 - VD Tribunal cantonal (2021)
CONTRAINTEDROIT PÉNAL, PRESSION, PROCÉDURE ÉCRITE, TENTATIVE DE SUICIDE, TENTATIVEDROIT PÉNAL, TENTATIVEEN GÉNÉRAL | 28 CC, 41 CO, 181 CP, 22 ad 181 CP, 22 CP, 34 CP, 42 al. 1 CP, 47 CP, 406 CPP